Risk assessment on plan layout for project mechanical workshop in Politeknik Kuching Sarawak - Sukindar, Nor Aiman; Ab Tahir, Aliff (Politeknik Kuching Sarawak, 2018)
Risk Assessment is very important to ensure safety in every aspect including operation, activities, plan layout and many more. The responsibilities to ensure the safety and health at the workplace lie with those who create the risk and with those who work with the risk. This study analyzes and identifies all possible hazards related to the plan layout in the Mechanical department’s project workshop in Politeknik Kuching Sarawak. Analysis of risk was recorded with the HIRARC Form. The probability was measured by referring to the history, interview and also by observation. Student timetables must also be taken into consideration when determining the likelihood of risk. Some recommendations and new plan layouts for the Project Workshop were proposed to ensure the risks remains in the acceptable level.